Microstructure characterization in a single isotactic polypropylene spherulite by synchrotron microfocus wide angle X-ray scattering. (25th April 2018) - Chang, Baobao; Schneider, Konrad; Patil, Nilesh; Roth, Stephan; Heinrich, Gert
Abstract: Position-resolved microstructure in a single spherulite of iPP is quantitatively studied by synchrotron microfocus wide angle X-ray scattering. The results show that the normal of mother lamellae in a spherulite is aligned mainly perpendicular to the radius, and the subsidiary daughter lamellae are inclined 80.75° with respect to that of the dominant mother lamellae. The crystallinity in the spherulite is in the range of 46%–56%, which is rarely influenced by the crystallization temperature. The ratio between the daughter lamellae and the mother lamellae is 0.18 when iPP crystallizes at 138 °C and it decreases to 0.11 as the crystallization temperature is decreased to 130 °C. The b- axis and c - axis in the mother lamellae tend to orient perpendicular to the radius direction, and the a -axis prefers to align in the radius direction. Graphical abstract: Image 1 Highlights: The alignment of mother and daughter lamellae in a spherulite of isotactic polypropylene is investigated. The ratio between daughter lamellae and mother lamellae is decreased with increasing crystallization temperature. The b - axis and c -axis in mother lamellae orient perpendicular to, and the a -axis orients in, the radius direction.